THE ROLE OF SUBJECTIVE NORM IN EXPLAINING JAWI ADOPTION AMONG INDIANS IN MALAYSIA - Nor Fadzilah bt Md Yusof,; Mohd Khairul Bin Abdul Ghani,; Nur Aulia Fahada binti Misaridin,; Wan Hashridz Rizal bin Wan Abu Bakar2, , (Journal of Islamic, Social, Economics and Development, 2021)
Jawi is the orthography used to write Malay since the Middle Ages, when it wasadapted from the Arabic script. It was introduced by Muslim traders and adapted to Malayphonology by using diacritics that changed six letters. After the Malaysian governmentannounced a plan to introduce jawi script at the basic level for Primary Four vernacular schoolpupils beginning 2020, the issue has fueled tension among educationists, school officials, andthe general public. Therefore, this study aims to identify the role of subjective norms inexplaining the intention to Jawi adoption among Indian community in Malaysia. This studywas conducted with a total of 192 respondents. The sampling technique used is non-probabilitysampling. The findings of the study prove that subjective norms has a positive and significantrelationship with the intention to Jawi adoption among Indian in Malaysia.